Expression of γ-H2AX Using Immunofluorescence Assay as an Adaptive Response of PBMC in Radiation Workers at Dharmais Cancer Hospital - Musthafa, Arifin; Djuita, Fielda; Kurnia, Iin (National Cancer Center - Dharmais Cancer Hospital, 2018)
Background: Exposure ionizing of radiation in radiation workers has the potential to cause DNA damage in the form of double strand break as the beginning of genomic instability. DNA damage can be observed with γ-H2AX as the biomarker of DNA double strand breaks (DSBs). The formation of γ-H2AX in the nucleus can occur after radiation exposure of 1 mGy. This study aims to determine the radiation effects in radiation work environments as a study of adaptive responses of peripheral blood mononuclear cell (PBMCs) after radiation by observing γ-H2AX foci expression.. Methods: Blood samples from nine radiation workers and nine non-radiation workers were irradiated with doses 0 Gy, 1 Gy, 1.5 Gy, and 2 Gy. Detection of γ-H2AX foci was done by immunofluorescence assay. The mean of γ-H2AX foci was counted in 50 PBMCs per sample. The comparison mean of γ-H2AX foci was analyzed using tindependent test. Result: Based on the result study, there were no significant differences in the number of γ-H2AX foci without treatment (p = 0.807). The results of study showed that the formation of 2-3 foci per cell after exposure of 2 Gy increases along with the increasing irradiation doses. Conclusion: The mean of index of γ-H2AX foci in PBMCs within normal limits between non-radiation workers and radiation workers and level of risk DSBs damage is relatively similar after exposure at doses 1 Gy, 1.5 Gy, and 2 Gy.